An investigation on the influence of Ginkgo biloba extract on tetracycline hepatotoxicity - Felek, S.; Yekeler, H.; Ocak, S.; Doymaz, M.Z.; Ilhan, N.; Killic, S.S. (My University, 1995)
In this study, the effects of Ginkgo biloba extract (GBE), a free radical scavenger, on tetracycline hepatotoxicity were determined. Animals (51 male, Balb/c mice) were divided into 3 experimental groups. In the first two groups, 2 g/l tetracycline and 2 g/l tetracycline plus 67 mg/l GBE were added to the drinking water, respectively. The last group of mice received only tap water. The expected doses of tetracycline and GBE in the first two groups, were 300 mg/kg/day and 10 mg/kg/day, respectively. Animals were given the drugs for 15 days. Later, the mice were killed, and liver and blood samples were collected. In the sera, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase activities were determined. Histopathological evaluation was carried out using the light microscope. Aspartate amino transferase, ALT, and alkaline phosphatase levels in the tetracycline group, were 354.4 ± 140.8 U/l, 85.6 ± 29.0 U/l, 118,1 ± 64.5 U/l, respectively. In the tetracycline plus GBE group, AST, ALT, and alkaline phosphatase levels were 291.4 ± 111.2 U/l, 67.0 ± 19.6 U/l, 113.8 ± 50.0 U/l, respectively. In the tap water group, AST, ALT, and alkaline phosphatase levels were 253.1 ± 78.0 U/l, 71.2 ± 23.4 U/l, 48.8 ± 42.4 U/l respectively. ALT activity was decreased significantly in the tetracycline plus GBE group (p < 0.05). AST and alkaline phosphatase levels were not decreased statistically (p > 0.05). In histopathological examination, no significant change was noticed in the tetracycline plus GBE group (p > 0.05). Our results indicate that GBE, when administered at 10 mg/kg dosage is able to reverse one of the most important hepatotoxicity parameters, namely the ALT activity. However, no significant change was observed in other biochemical and histopathological parameters. At higher doses, it is likely that a more pronounced influence on tetracycline hepatotoxicity might be exerted by GBE. This point needs to be studied in a greater detail.
Keywords: antibiotic; free radical scavenger; Ginkgo biloba extract; hepatotoxicity; tetracycline